The cognitive function and taekwondo-specific kick performance of taekwondo athletes at different hydration statuses - Zheng, A.-C.; He, C.-S.; Lu, C.-C.; Hung, B.-L.; Chou, K.-M.; Fang, S.-H. (International Journal of Sports Physiology and Performance, 2024)
Purpose Successful participation in taekwondo (TKD) requires athletes to possess quick decision-making abilities and demonstrate technical proficiency during competition. Dehydration, occurring during both training and competition, is widely recognized to have various negative effects.